Chemical characteristics of wildfire ash across the globe and their environmental and socio-economic implications - Carmen Sanchez-Garcia (Environment International, 2023)
The mobilisation of potentially harmful chemical constituents in wildfire ash can be a major consequence of wildfires, posing widespread societal risks. Knowledge of wildfire ash chemical composition is crucial to anticipate and mitigate these risks. Here we present a comprehensive dataset on the chemical characteristics of a wide range of wildfire ashes (42 types and a total of 148 samples) from wildfires across the globe and examine their potential societal and environmentalimplications. An extensive review of studies analysing chemical composition in ash was also performed to complement and compare our ash dataset. Most ashes in our dataset had an alkaline reaction (mean pH 8.8, ranging between 6 and 11.2). Important constituents of wildfire ash were organic carbon (mean: 204 g kg−1), calcium, aluminium, and iron (mean: 47.9, 17.9 and 17.1 g kg−1). Mean nitrogen and phosphorus ranged between 1 and 25 g kg−1, and between 0.2 and9.9 g kg−1, respectively. The largest concentrations of metals of concern for human and ecosystem health were observed for manganese (mean: 1488 mg kg−1; three ecosystems > 1000 mg kg−1), zinc (mean: 181 mg kg−1; two ecosystems > 500 mg kg−1) and lead (mean: 66.9 mg kg−1; two ecosystems > 200 mg kg−1). Burn severity and sampling timing were key factors influencing ash chemical characteristics like pH, carbon and nitrogen concentrations. The highest readily dissolvable fractions (as a % of ash dry weight) in water were observed for sodium (18 %) and magnesium (11.4 %). Although concentrations of elements of concern were very close to, or exceeded international contamination standards in some ashes, the actual effect of ash will depend on factors likeash loads and the dilution into environmental matrices such as water, soil and sediment. Our approach can serve as an initial methodological standardisation of wildfire ash sampling and chemical analysis protocols.